Resistance Profiles of Salmonella Isolates Exposed to Stresses and the Expression of Small Non-coding RNAs - Wang, Huhu; Huang, Mingyuan; Zeng, Xianming; Peng, Bing; Xu, Xinglian; Zhou, Guanghong (Frontiers in Microbiology, 2020)
Salmonella can resist various stresses and survive during food processing, storage, and distribution, resulting in potential health risks to consumers. Therefore, analysis of bacterial survival profiles under various environmental stresses is necessary. In this study, we examined the resistance profiles of five Salmonella isolates (Agona, Infantis, Typhimurium, Enteritidis, and a standard strain (ATCC 13076)) to acidic, hyperosmotic, and oxidative stresses, and evaluated differences in the relative expression of noncoding small RNAs, including CyaR, MicC, MicA, InvR, RybB, and DsrA, induced by specific stresses. The results indicated that although all tested strains displayed a certain resistance to stresses, there was great diversity in stress resistance among the strains. According to the reduction numbers of cell exposed to stress for 3 hours, the S. Enteritidis showed the highest resistance to acidic and hyperosmotic stresses, whereas S. ATCC 13076 showed the greatest resistance to oxidative stress, with less than 0.1 Log CFU/mL of cells reduction. Greater resistance of cells to acidic, hyperosmotic, and oxidative stresses was observed within 1 h, after 2 h, and from 1 to 2 h, respectively. The relative expression of sRNAs depended on the isolate for each stress; acidic exposure for the tested isolates induced high expression levels of DsrA, MicC, InvR, RybB, MicA, and CyaR. The sRNA RybB, associated with sigma E and outer membrane protein in bacteria, showed a fold-change of greater than 7 in S. Enteritidis exposed to the tested stresses. CyaR and InvR involved in general stress responses and stress adaptation were also induced to show high expression levels of Salmonella exposed to hyperosmotic stress. Overall, our findings demonstrated that the behaviors of Salmonella under specific stresses varied according to strain and were likely not related to other profiles. The finding also provided insights into the survival of Salmonella subjected to short-term stresses and for controlling Salmonella in the food industry.